Poultry products enriched with nutricines have beneficial effects on human health - Gordana Kralik; Zlata Kralik (Medicinski glasnik, 2017)
The paper presents nutritive value of broiler meat and table eggs, as these animal products are used for human nutrition on a daily basis. In the Republic of Croatia, average consumption of poultry meat amounts to 18.3 kg and to 160 eggs per capita.The most quality parts of broiler carcass are breasts and drumsticks with thighs. Breast muscles contain 21-23% protein, 1.90-1.97% fat, 75.28- 76.01% water and 0.74-0.77% collagen. Thigh muscles contain 4.70-6.05% fat, 19.03-19.93% protein and 0.91-1.13% collagen. White meat contains more potassium and magnesium and less zinc and iron than dark meat. In 100 g of edible egg part there is 12.5-13.5 g protein, 10.7-11.6 g fat and 1.0-1.1 g minerals. Caloric valueof eggs is 167 Kcal. Eggs contain high amount of essential amino acids, especially leucine, isoleucine, lysine, arginine, valine and phenylalanine. Furthermore, eggs contain many vitamins, especially A, D, E, K and B-complex, as well as various macroelements and microelements. Eggs and meat enriched with one or more functional ingredients - nutricines (polyunsaturated fatty acids n-3), eicosapentaenoic acid, docosahexaenoic acid, selenium and lutein) meet the criteria of functional food because of their added value and benefits for human health.
Keywords: eggs; meat; EPA; DHA; cardiovascular disease